Lead optimization of selective tubulin inhibitors as anti-trypanosomal agents. Issue 8 (15th April 2019) - Zhao, Anran; Li, Yaxin; Orahoske, Cody M.; Schnur, Brittny; Sabbagh, Abboud; Zhang, Wenjing; Li, Bibo; Su, Bin
Graphical abstract: Highlights: Selective tubulin inhibitors against trypanosomal cells were synthesized. The compounds have only two aromatic moieties compared to the lead with four aromatic moieties. Two new analog showed high selectivity and potency against the proliferation of trypanosome cells. The compounds decreased tubulin polymerization in trypanosome cells. Abstract: Previously synthesized tubulin inhibitors showed promising in vitro selectivity and activity against Human African Trypanosomiasis. Current aim is to improve the ligand efficiency and reduce overall hydrophobicity of the compounds, by lead optimization. Via combinatorial chemistry, 60 new analogs were synthesized. For biological assay Trypanosoma brucei brucei Lister 427 cell line were used as the parasite model and for the host model human embryonic kidney cell line HEK-293 and mouse macrophage cell line RAW 264.7 were used to test efficacy. Of the newly synthesized compounds 5, 39, 40, and 57 exhibited IC50 s below 5 µM inhibiting the growth of trypanosome cells and not harming the mammalian cells at equipotent concentration. Comparably, the newly synthesized compounds have a reduced amount of aromatic moieties resulting in a decrease in molecular weight. Due to importance of tubulin polymerization during protozoan life cycle its activity was assessed by western blot analyses. Our results indicated that compound 5 had a profound effect on tubulin function. A detailed structure activity relationship (SAR) was summarized that will be used to guide future lead optimization.